An Analysis of Tiny Houses through a Viewpoint on Preferences, Satisfaction, and Expectations of Residents - Elif Çay; Miray Gür (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In recent years, there has been a significant increase in the prevalence of tiny houses, reflecting the worldwide trend of this favored living option. Scientific study on tiny houses has experienced a modest global growth in recent years, even though the notion of tiny houses has only been lately introduced to Turkish literature. Information on tiny houses is mostly available through various media channels, including television, newspapers, magazines, and social media platforms, in our country. This article seeks to examine the concept and current popularity of tiny houses, while also assessing user preferences and levels of satisfaction. User satisfaction was evaluated based on data obtained from twenty interviews conducted with owners of small-scale dwellings. The primary results suggest that individuals who exhibit a preference for residing in tiny houses have an awareness of the disparities and challenges they are likely to face. The appealing qualities of the house extends beyond its physical appearance. The mere existence of a location, regardless of its size, situated in a calm and peaceful environment, far from chaos and confusion, where individuals have a sense of belonging, is enough to satisfy their needs.